The code document's structure and analysis - Reeves, Stuart (2006)
The purpose of this paper is twofold. Firstly it presents a preliminary and ethnomethodologically-informed analysis of the way in which the growing structure of a particular program's code was ongoingly derived from its earliest stages. This was motivated by an interest in how the detailed structure of completed program `emerged from nothing' as a product of the concrete practices of the programmer within the framework afforded by the language. The analysis is broken down into three sections that discuss: the beginnings of the program's structure; the incremental development of structure; and finally the code productions that constitute the structure and the importance of the programmer's stock of knowledge. The discussion attempts to understand and describe the emerging structure of code rather than focus on generating `requirements' for supporting the production of that structure. Due to time and space constraints, however, only a relatively cursory examination of these features was possible. Secondly the paper presents some thoughts on the difficulties associated with the analytic---in particular ethnographic---study of code, drawing on general problems as well as issues arising from the difficulties and failings encountered as part of the analysis presented in the first section.